The effect of training doctors in communication skills on women's satisfaction with doctor–woman relationship during labour and delivery: a stepped wedge cluster randomised trial in Damascus. Issue 8 (14th August 2013) - Bashour, Hyam N; Kanaan, Mona; Kharouf, Mayada H; Abdulsalam, Asmaa A; Tabbaa, Mohammed A; Cheikha, Salah A
Abstract : Objectives: To determine the effect of training residents in interpersonal and communication skills on women's satisfaction with doctor–woman relationship in labour and delivery rooms. Design: A stepped wedge cluster randomised trial. Setting: 4 tertiary care teaching maternity hospitals in Damascus, Syria. Participants: 2000 women who gave birth to a living baby in the four study hospitals and consented to participate in the intervention took part in the study. Women with difficult labour and high-risk pregnancies were excluded. All were interviewed at home after discharge. Interventions: A specially designed training package in communication skills was delivered to all resident doctors at the four hospitals. Primary outcome measures: The main outcome measure was women's satisfaction with interpersonal relationships in labour and delivery rooms measured via a series of questions on a Likert scale modified from the Medical Interview Satisfaction Scale. Results: At the individual level, the mean for the average satisfaction score was 3.23 (SD 0.72) of a possible score of 5 in the control group and 3.42 (SD 0.73) in the intervention group. Using generalised linear mixed models, we were unable to detect a difference between the mean for the average satisfaction score of women in the intervention arm and that of women in the control arm; the 95% CI associated with the effect of the intervention ranged from –0.08 to 0.15. Conclusions: Despite slight changes in the observed residents' communication skills, the training package in communication skills does not seem to be associated with higher satisfaction scores of women. This raises the question of whether training individuals without further structural changes in the delivery of care and without further reinforcement of the training can have an impact on improving the quality of doctor–patient communication. Trial Registration Number: ISRCTN80243969